Day of solidarity with the people of Mozambique, September 25 - Lazaro (OSPAAAL (Organization of Solidarity with the People of Asia, Africa and Latin America), 1970)
Symbol of Portuguese colonialism pierced by arrows; FRELIMO written on them (Mozambique Liberation Front) Poster in four languages advertising day of solidarity with Mozambique, 25 September PO-1596